THE USE OF TASK-BASED INSTRUCTION TO IMPROVE SPEAKING SKILL TO THE SECOND SEMESTER STUDENTS OF STKIP SILIWANGI BANDUNG ON THE ACADEMIC YEAR OF 2014-2015 - Ningtyas Orilina Argawati; Trisnendri Syahrizal (Jurnal Ilmiah P2M STKIP Siliwangi, 2016)
The speaking capability of the second-semester students in STKIP Siliwangi BANDUNG can still be improved since they have the chance to change. The college location, the lecturers, and the students’ capability itself enable them to get the best result of the study. However, they still speak with hesitation since they feel not confidence to speak, or in the other way they lack motivation. Therefore, this study aims to improve the students speaking skill through Task-based Instruction. This method relays on the use of task to gather students and they have to accomplish the task with their own way. This study consists of two cycles, each cycle consists of a pre-test, two meetings treatment, and post-test. From the data taken, the result tends to be good. There is an improvement in both the students’ ability and motivation. The improvement can be seen on their increasing on their speaking score and in their way, they perform their speaking. In conclusion, a task can help students to study by their own. It works when it was implemented on the second students of STKIP Siliwangi Bandung.Keywords: Action Research, Speaking Skill, Task-Based Instruction